2018
DOI: 10.1115/1.4040615
|View full text |Cite
|
Sign up to set email alerts
|

Process Mapping and In-Process Monitoring of Porosity in Laser Powder Bed Fusion Using Layerwise Optical Imaging

Abstract: The goal of this work is to understand the effect of process conditions on lack of fusion porosity in parts made using laser powder bed fusion (LPBF) additive manufacturing (AM) process, and subsequently, to detect the onset of process conditions that lead to lack of fusion-related porosity from in-process sensor data. In pursuit of this goal, the objectives of this work are twofold: (1) quantify the count (number), size and location of pores as a function of three LPBF process parameters, namely, the hatch sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(28 citation statements)
references
References 67 publications
0
22
0
Order By: Relevance
“…The proposed method is applied to a case study example using probe vehicle speeds from several links in downtown Philadelphia, Pennsylvania. The results are used to identify communities of links which share similar spatiotemporal patterns using graph theory methods ( 16 , 17 ). These communities are shown to be remarkably consistent across the days in a week—and even throughout a day—suggesting that they represent relationships caused by the underlying traffic network structure.…”
mentioning
confidence: 99%
“…The proposed method is applied to a case study example using probe vehicle speeds from several links in downtown Philadelphia, Pennsylvania. The results are used to identify communities of links which share similar spatiotemporal patterns using graph theory methods ( 16 , 17 ). These communities are shown to be remarkably consistent across the days in a week—and even throughout a day—suggesting that they represent relationships caused by the underlying traffic network structure.…”
mentioning
confidence: 99%
“…The proposed control and awareness module is supported by several research studies that focused on the development of an online monitoring and control (OMC) system to detect and isolate defects and to manufacture parts with particular desired qualities (Armini & Chang 2018b;Imani et al 2018;Yao et al 2018). A particularly important aspect of the proposed framework is that it may accommodate any combination of ML and SPC techniques for fault detection.…”
Section: Discussion On Implementation and Validationmentioning
confidence: 99%
“…The authors demonstrated that their approach performed at par to highly complex CNN and LSTM-RNN models and required nearly 1/10th of the computation time. Similarly, Imani et al (2018) demonstrated the ability of an ANN to predict laser powder bed fusion process parameter regimes using layer wise optical images. Kumar and Maji (2020) in their recent work employed a Genetic Algorithm-based (GA) framework for extracting the optimal process parameters of wire-arc additive manufacturing process.…”
Section: Prior Work Challenges and Noveltymentioning
confidence: 99%